UNDERSTANDING GEOLOGICALLY COMPLEX RESERVOIR ZONE USING MULTI TANK MATERIAL BALANCE ANALYSIS FOR BETTER RESERVES ESTIMATION - REKSI DWITANTRA SUTOYO, HANDITA
This study proves the capability of dynamic modeling to assist reserve evaluation based on static and dynamic data. Dynamic modeling in this field uses a zero dimensional material balance analysis. Starting from reservoir screening based on static modeling results, this review of static modeling results will give us an initial guess and conception of possible compartments formed in these reservoirs. Later, dynamic data i.e. pressure and production history will be analyzed to know any possible compartments. Integration of both static and dynamic data will be incorporated as an input for dynamic modeling by using material balance. The use of multi tank material balance analysis is introduced as a new method for modeling complex reservoirs. Application of this method gives a big impact to represent these reservoirs behavior dynamically. This study provides insights on different compartments existed in some reservoirs. Multi tank material balance analysis give a dynamic model that represent reservoir dynamic behavior. Furthermore, reserve evaluation and reservoir performance prediction can be an output of this dynamic modeling. The results of this evaluation gives 21% of 24 modeled reservoirs give more than 30% of absolute error with referenced original oil in-place, and 75% of 24 modeled reservoirs give more than 30% of absolute error with referenced initial gas in-place. This modeling results will be used as a guideline for future studies especially for initial gas in-place value determination.